An economic evaluation of anonymised information sharing in a partnership between health services, police and local government for preventing violence-related injury. Issue 2 (18th September 2013) - Florence, Curtis; Shepherd, Jonathan; Brennan, Iain; Simon, Thomas R
Abstract : Objective: To assess the costs and benefits of a partnership between health services, police and local government shown to reduce violence-related injury. Methods: Benefit-cost analysis. Results: Anonymised information sharing and use led to a reduction in wounding recorded by the police that reduced the economic and social costs of violence by £6.9 million in 2007 compared with the costs the intervention city, Cardiff UK, would have experienced in the absence of the programme. This includes a gross cost reduction of £1.25 million to the health service and £1.62 million to the criminal justice system in 2007. By contrast, the costs associated with the programme were modest: setup costs of software modifications and prevention strategies were £107 769, while the annual operating costs of the system were estimated as £210 433 (2003 UK pound). The cumulative social benefit-cost ratio of the programme from 2003 to 2007 was £82 in benefits for each pound spent on the programme, including a benefit-cost ratio of 14.80 for the health service and 19.1 for the criminal justice system. Each of these benefit-cost ratios is above 1 across a wide range of sensitivity analyses. Conclusions: An effective information-sharing partnership between health services, police and local government in Cardiff, UK, led to substantial cost savings for the health service and the criminal justice system compared with 14 other cities in England and Wales designated as similar by the UK government where this intervention was not implemented.